Turbulent erosion of a subducting intrusion in the Western Mediterranean Sea - Giovanni Testa; Mathieu Dever; Mara Freilich; Amala Mahadevan; T. M. Shaun Johnston; Lorenzo Pasculli; Francesco M. Falcieri (Ocean Science, 2025)
Frontal zones within the Western Alboran Gyre (WAG) are characterized by a density gradient resulting from the convergence of Atlantic and Mediterranean waters. Subduction along isopycnals at the WAG periphery can play a crucial role in upper-ocean ventilation and influences its stratification and biogeochemical cycles. In 2019, physical parameters (comprising temperature, salinity, turbulent kinetic energy dissipation rates) and biogeochemical data (oxygen and chlorophyll a) profiles were collected in transects along the northern edge of the WAG. Several intrusions of subducted water with elevated oxygen, chlorophyll a, and spice anomaly were identified towards the center of the anticyclone. These features had elevated kinetic energy dissipation rates on both their upper and lower boundaries. Analysis of the turbulent fluxes involving heat, salt, oxygen, and chlorophyll a demonstrated a net flux of physical and biogeochemical properties from the intrusions to the surrounding ocean. Either the turbulent or diffusive convection mixing contributed to the observed dilution of the intrusion. Other factors (e.g., water column density stability, variability of the photic layer depth, and organic matter degradation) likely played a role in these dynamics. Enhanced comprehension of the persistence and extent of these features might lead to an improved quantitative parameterization of relevant physical and biogeochemical properties involved in subduction within the study zone.

Geodiversity of proglacial areas and implications for geosystem services: A review - Irene Maria Bollati; Cristina Viani; Anna Masseroli; Giovanni Mortara; Bruno Testa; Gianluca Tronti; Manuela Pelfini; Emmanuel Reynard (Geomorphology, 2023)

Nasal Microbiome in COVID-19: A Potential Role of Corynebacterium in Anosmia - Carmela Nardelli; Giovanni Luca Scaglione; Domenico Testa; Mario Setaro; Filippo Russo; Carmela Di Domenico; Lidia Atripaldi; Massimo Zollo; Federica Corrado; Paola Salvatore; Biagio Pinchera; Ivan Gentile; et al. (Current Microbiology, 2023)
The evolution and the development of the symptoms of Coronavirus disease 19 (COVID-19) are due to different factors, where the microbiome plays a relevant role. The possible relationships between the gut, lung, nasopharyngeal, and oral microbiome with COVID-19 have been investigated. We analyzed the nasal microbiome of both positive and negative SARS-CoV-2 individuals, showing differences in terms of bacterial composition in this niche of respiratory tract. The microbiota solution A (Arrow Diagnostics) was used to cover the hypervariable V1–V3 regions of the bacterial 16S rRNA gene. MicrobAT Suite and MicrobiomeAnalyst program were used to identify the operational taxonomic units (OTUs) and to perform the statistical analysis, respectively. The main taxa identified in nasal microbiome of COVID-19 patients and in Healthy Control subjects belonged to three distinct phyla: Proteobacteria (HC = 14%, Cov19 = 35.8%), Firmicutes (HC = 28.8%, Cov19 = 30.6%), and Actinobacteria (HC = 56.7%, Cov19 = 14.4%) with a relative abundance > 1% in all groups. A significant reduction of Actinobacteria in Cov19 group compared to controls ( P < 0.001, FDR = 0.01) was found. The significant reduction of Actinobacteria was identified in all taxonomic levels down to the genus ( P < 0.01) using the ANOVA test. Indeed, a significantly reduced relative abundance of Corynebacterium was found in the patients compared to healthy controls ( P = 0.001). Reduced abundance of Corynebacterium has been widely associated with anosmia, a common symptom of COVID-19 as suffered from our patients. Contrastingly, the Corynebacterium genus was highly represented in the nasal mucosa of healthy subjects. Further investigations on larger cohorts are necessary to establish functional relationships between nasal microbiota content and clinical features of COVID-19.

Physical and Biogeochemical Regionalization of the Southern Ocean and the CCAMLR Zone 48.1 - Giovanni Testa; Andrea Piñones; Leonardo R. Castro (Frontiers in Marine Science, 2021)
The Southern Ocean plays a major role in the Earth’s climate, provides fisheries products and help the maintenance of biodiversity. The degree of correspondence between physical and biogeochemical spatial variability and regionalization were investigated by calculating the main physical factors that statistically explained the biogeochemical variability within the Southern Ocean and the 48.1 zone of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). The mean value of physical and biogeochemical variables was estimated during austral summer within a grid of 1° × 1° south of 50°S. The regionalization was developed using both non-hierarchical and hierarchical clustering method, whereas BIO-ENV package and distance-based redundancy analysis (db-RDA) were applied in order to calculate which physical factors primarily explained the biogeochemical spatial variability. A total of 12 physical and 18 biogeochemical significant clusters were identified for the Southern Ocean (alpha: 0.05). The combination of bathymetry and sea ice coverage majorly explained biogeochemical variability (Spearman rank correlation coefficient: 0.68) and db-RDA indicated that physical variables expressed the 60.1% of biogeochemical variance. On the other hand, 14 physical and 16 biogeochemical significant clusters were identified for 48.1 CCAMLR zone. Bathymetry was the main factor explaining biogeochemical variability (Spearman coefficient: 0.81) and db-RDA analysis resulted in 77.1% of biogeochemical variance. The correspondence between physical and biogeochemical regions was higher for CCAMLR 48.1 zone with respect to the whole Southern Ocean. Our results provide useful information for both Southern Ocean and CCAMLR 48.1 zone ecosystem management and modeling parametrization.

Fermentation and Anaerobic Oxidation of Organic Carbon in the Oxygen Minimum Zone of the Upwelling Ecosystem Off Concepción, in Central Chile - Benjamín M. Srain; Marcus Sobarzo; Giovanni Daneri; Humberto E. González; Giovanni Testa; Laura Farías; Alex Schwarz; Norma Pérez; Silvio Pantoja-Gutiérrez (Frontiers in Marine Science, 2020)

Acute flaccid paralysis due to Echovirus 30 in an immunosuppressed transplant recipient - Eleonora Mauri; Antonio Mastrangelo; Sara Testa; Laura Pellegrinelli; Elena Pariani; Sandro Binda; Fabio Triulzi; Sergio Barbieri; Cristina Bana; Giovanni Montini; Robertino Dilena (Journal of NeuroVirology, 2020)

Temporal Variability in Net Primary Production in an Upwelling Area off Central Chile (36°S) - Giovanni Testa; Italo Masotti; Laura Farías (Frontiers in Marine Science, 2018)

Soil Erosion Mitigation by Perennial Species Under Mediterranean Environment - Salvatore Luciano Cosentino; Venera Copani; Giovanni Scalici; Danilo Scordia; Giorgio Testa (BioEnergy Research, 2015)

Proteasome inhibitors sensitize ovarian cancer cells to TRAIL induced apoptosis - Ernestina Saulle; Alessia Petronelli; Luca Pasquini; Eleonora Petrucci; Gualtiero Mariani; Mauro Biffoni; Gianluigi Ferretti; Giovanni Scambia; Pierluigi Benedetti-Panici; Francesco Cognetti; Robin Humphreys; Cesare Peschle; et al. (Apoptosis, 2007)